The r1 relaxivity and T1 imaging properties of dendrimer-based manganese and gadolinium chelators in magnetic resonance imaging - Liu, Kai; Liu, Changcun; Xia, Jindong (Frontiers in Bioengineering and Biotechnology, 2022)
We report the preparation, and characterization of gadolinium (Gd)-loaded or manganese (Mn)-loaded dendrimers as well as Gd-loaded dendrimer-entrapped gold nanoparticles for the relationship between the number of metal ion chelator and the r1 relaxivity. In this study, amine-terminated generation five poly (amidoamine) dendrimers (G5.NH2) modified with a different number of DOTA-NHS chelator was used to chelate Gd and Mn ion. Then the remainder amine groups were completely acetylated through an acetylation process. Followed, using the materials with better r1 relaxivity and T1-weighted imaging performance as the templates to synthesize gadolinium-loaded dendrimer-entrapped gold nanoparticles (Gd-Au DENP). The formed Gd, Mn chelator, and Gd-Au DENPs were characterized via different techniques. We show that the r1 relaxivity and T1 imaging increased with the more number of Gd and Mn ions loaded on the G5.NH2 and the acetylation process have a certain extent an effect on the relaxivity and imaging properties. After being entrapped with Au NPs the r1 relaxivity and T1-weighted imaging performance of Gd-Au DENPs decreased with the more Au NPs loaded. The systematic study of relaxivity and T1-weighted imaging of Gd, Mn, and Gd-Au DENP chelator will afford a theoretical basis for constructing multifunction dual-mode contrast agents.